Investigation of reduction of magnetite based carbon composite pellets under semi-fusion conditions - Benkli, Yunus Emre; Boyrazli, Mustafa; Senoz, Guzide Meltem Lule; Cizmecioglu, Zeki (Oficyna Wydawnicza Politechniki Wroclawskiej, 2018)
In this study, carbon composite pellets were exposed to a reduction test under low temperature and semi-fusion conditions in which iron was melted without a solid form of slag deteriorated. The purpose of the reduction experiments under the semi-fusion condition was to produce an iron nugget which had physical and chemical properties similar to blast furnace pig iron at lower temperatures. These nuggets were produced from pellets that were made from a mixture of iron oxide, coke, flux, and a binder. These nuggets heated in a furnace with a chamber temperature of 1330 degrees C. The produced dried carbon composite pellets were melted and carbureted in a single-stage process. In this study, three distinct products were produced as a function of furnace residence time at fixed furnace temperature (1330 degrees C). These products were direct reduced iron (DRI), transition direct reduced iron (TDRI), and iron nuggets produced at residence times 8-24, 32-40 min, and 48 min, respectively. The iron nugget produced had a high apparent density (6.903 g/cm(3)), high micro hardness values (328 HV), high iron content (92.7% Fe), and was similar to blast furnace pig iron.
Keywords: iron ore; pelletizing; cold bonded composite pellet; iron nugget